(untitled) (Studia Politica. Romanian Political Science Review, 2025)
The book opens with an artifice that stimulates the reader’s curiosity: “at the same time and everywhere “is an attention grabber that reveals the meaning and role of the book: a chronicle of different perspectives on the seminal events for the last two years. What prefigures the reading of the book is also mentioned in the title, as a leitmotif and a captatio benevolentiae: the turning point recalls another important theme recurrently mentioned by the former President of the United States Joe Biden in his speeches: the “inflection point.” This inflection point is constituted, in fact, by successive transformations undergone by the contemporary world as an acceleration of History, with a capital letter, and to which we become both witnesses, and participants, in a deeply polarizing, radicalized environment, directly experiencing every action almost immediately. This inflection of history written before our eyes has different meanings, which can be discovered by observing some details or facts that the author proves he can understand with acuity, throughout this volume.